A 30,000-year continuous record of glacial history and water balance from Fish Lake, Utah documents the onset, development, and demise of LGM glaciation - M.B. Abbott; D.W. Marchetti; L. Anderson; J.S. Stoner; B.T. Reilly; J.L. Morris; A.R. Brunelle; V.A. Kraklow; M.J. Power; M.S. Finkenbinder; D.J. Larsen; R.G. Hatfield; et al. (Quaternary Science Reviews, 2026)

Corrigendum to “Temperature and precipitation source variability and glacial dynamics in the southwestern United States at Fish Lake, Utah, since late MIS 4” [Quat. Sci. Rev. 379 (2026) 109919] - J.R. Vornlocher; M.D. O'Beirne; A. DePaoli; J.P. Werne; D.W. Marchetti; L. Anderson; A. Brunelle; J.S. Stoner; B.T. Reilly; J.L. Morris; V.A. Kraklow; M.J. Power; et al. (Quaternary Science Reviews, 2026)

Temperature and precipitation source variability and glacial dynamics in the southwestern United States at Fish Lake, Utah, since late MIS 4 - J.R. Vornlocher; M.D. O'Beirne; A. DePaoli; J.P. Werne; D.W. Marchetti; L. Anderson; A. Brunelle; J.S. Stoner; B.T. Reilly; J.L. Morris; V.A. Kraklow; M.J. Power; et al. (Quaternary Science Reviews, 2026)

P35-02 An Optimized Strategy for the Assessment of T-Modality in the Identification of Endocrine Disruptors - G. Marchetti; A.L. Guillot; J. Lhermite; C. Pais Do Amaral (Toxicology Letters, 2025)

Palynological assemblages from the 2nd tectono-sedimentary cycle of the Southern Alps: New constraints for the onset of the Alpine cycle and regional-global inferences - A. Spina; E. Capezzuoli; N. Gretter; L. Marchetti; C. Corradini; N. Degl'Innocenti; R. Scarani; A. Ronchi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Alkali, thermal, or thermo-alkali pre-treatment to improve the anaerobic digestion of poly(lactic acid)? - C. Vasmara; G. Cazaudehore; E. Ceotto; R. Marchetti; C. Sambusiti; F. Monlau (Water Research, 2024)

Drought responses of Italian silver fir provenances in a climate change perspective - S.D. Oggioni; L.M.W. Rossi; C. Avanzi; M. Marchetti; A. Piotti; G. Vacchiano (Dendrochronologia, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

The impact of habitat complexity on the structure of marine sessile communities and larvae supply - Otávio C. Marchetti; Silvia Titotto; Gustavo M. Dias (Marine Environmental Research, 2024)

Duplex sequencing provides detailed characterization of mutation frequencies and spectra in the bone marrow of MutaMouse males exposed to procarbazine hydrochloride - Annette E. Dodge; Danielle P. M. LeBlanc; Gu Zhou; Andrew Williams; Matthew J. Meier; Phu Van; Fang Yin Lo; Charles C. Valentine III; Jesse J. Salk; Carole L. Yauk; Francesco Marchetti (Archives of Toxicology, 2023)
Mutagenicity testing is an essential component of health safety assessment. Duplex Sequencing (DS), an emerging high-accuracy DNA sequencing technology, may provide substantial advantages over conventional mutagenicity assays. DS could be used to eliminate reliance on standalone reporter assays and provide mechanistic information alongside mutation frequency (MF) data. However, the performance of DS must be thoroughly assessed before it can be routinely implemented for standard testing. We used DS to study spontaneous and procarbazine (PRC)-induced mutations in the bone marrow (BM) of MutaMouse males across a panel of 20 diverse genomic targets. Mice were exposed to 0, 6.25, 12.5, or 25 mg/kg-bw/day for 28 days by oral gavage and BM sampled 42 days post-exposure. Results were compared with those obtained using the conventional lacZ viral plaque assay on the same samples. DS detected significant increases in mutation frequencies and changes to mutation spectra at all PRC doses. Low intra-group variability within DS samples allowed for detection of increases at lower doses than the lacZ assay. While the lacZ assay initially yielded a higher fold-change in mutant frequency than DS, inclusion of clonal mutations in DS mutation frequencies reduced this discrepancy. Power analyses suggested that three animals per dose group and 500 million duplex base pairs per sample is sufficient to detect a 1.5-fold increase in mutations with > 80% power. Overall, we demonstrate several advantages of DS over classical mutagenicity assays and provide data to support efforts to identify optimal study designs for the application of DS as a regulatory test.

Error-corrected duplex sequencing enables direct detection and quantification of mutations in human TK6 cells with strong inter-laboratory consistency - Eunnara Cho; Carol D. Swartz; Andrew Williams; Miriam V. Rivas; Leslie Recio; Kristine L. Witt; Elizabeth K. Schmidt; Jeffry Yaplee; Thomas H. Smith; Phu Van; Fang Yin Lo; Charles C. Valentine; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Invasive frogs show persistent physiological differences to elevation and acclimate to colder temperatures - Jack R. Marchetti; Karen H. Beard; Emily E. Virgin; Erin L. Lewis; Steven C. Hess; Kwanho C. Ki; Layne O. Sermersheim; Adriana P. Furtado; Susannah S. French (Journal of Thermal Biology, 2023)

The erythrocyte sedimentation rate (ESR) in canine inflammation - E. Gori; A. Pierini; A. Pasquini; D. Diamanti; C. Carletti; G. Lubas; V. Marchetti (The Veterinary Journal, 2023)

Anti-Müllerian hormone in queens: Serum concentrations and total ovarian follicle population - C. Lapuente; M. Faya; P.G. Blanco; M. Grisolia-Romero; C. Marchetti; C. Gobello (Theriogenology, 2023)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

Population Pharmacokinetics of Intracellular 5-Fluorouridine 5′-Triphosphate and its Relationship with Hand-and-Foot Syndrome in Patients Treated with Capecitabine - Julie M. Janssen; Bart A. W. Jacobs; Jeroen Roosendaal; Ellen J. B. Derissen; Serena Marchetti; Jos H. Beijnen; Alwin D. R. Huitema; Thomas P. C. Dorlo (The AAPS Journal, 2021)

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The iron limitation mosaic in the California Current System: Factors governing Fe availability in the shelf/near‐shelf region - C. P. Till; J. R. Solomon; N. R. Cohen; R. H. Lampe; A. Marchetti; T. H. Coale; K. W. Bruland (Limnology and Oceanography, 2019)
The California Current System is a productive eastern boundary region off the coasts of Washington, Oregon, and California. There is strong seasonality to the region, with high levels of rainfall and river input to the coastal ocean during the winter season, and coastal and Ekman upwelling during the spring and summer. Iron (Fe) input to the coastal ocean during the winter months can be stored in the continental shelf mud belts and then be delivered to the surface ocean by upwelling in the spring and summer. There have been a number of studies providing strong evidence of Fe‐limitation of diatom growth occurring in regions of the California Current System off of California, and the occurrence of Fe‐limitation has been linked with narrow continental shelf mud belt width and low river input. We provide evidence for potential Fe‐limitation of diatoms off the southern coast of Oregon in July 2014, just off the shelf break near Cape Blanco in a region with moderate shelf width and river input. Since eastern boundary regions account for a disproportionally large amount of global primary production, this observation of potential Fe‐limitation in an unexpected near‐shore region of the California Current System has implications for global models of primary productivity. In order to re‐evaluate the factors impacting Fe availability, we utilize satellite imagery to compare with historical datasets, and show that unexpected levels of Fe can often be explained by eddies, plumes of upwelled water moving offshore, or lack of recent upwelling.

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Toward an Improved Representation of Middle Atmospheric Dynamics Thanks to the ARISE Project - E. Blanc; L. Ceranna; A. Hauchecorne; A. Charlton-Perez; E. Marchetti; L. G. Evers; T. Kvaerna; J. Lastovicka; L. Eliasson; N. B. Crosby; P. Blanc-Benon; A. Le Pichon; et al. (Surveys in Geophysics, 2018)

Anthropogenic impact in the Maya Lowlands of Petén, Guatemala, during the last 5500 years - D. Battistel; M. Roman; A. Marchetti; N. M. Kehrwald; M. Radaelli; E. Balliana; G. Toscano; C. Barbante (Journal of Quaternary Science, 2018)
Trace and rare earth elements from a sediment core from Lake Petén Itzá (Guatemala) depict the geochemical dynamics affecting the lake from ∼5500 a BP to the present. This timing encompasses the Preclassic (4000–1700 a BP) and Classic Periods (1700−1000 a BP) when thriving Maya societies extensively cleared land for agriculture. We demonstrate that this land use occurred during times of increased precipitation, where both processes resulted in increased erosion. Rare earth element ratios depict high precipitation rates between 3000 and 1000 a BP, correlating with an increase in allochthonous silicate input and low organic carbon in the ‘Maya Clay’ stratigraphic section, where this layer is ascribed to intensive anthropogenic land use. Cesium anomalies provide additional evidence for runoff due to high rainfalls and amplified by anthropogenic impacts. The Petén Itzá core contains anomalous spikes of arsenic and mercury, and these peaks correspond to documented volcanic eruptions and therefore are probably natural. The geochemical composition of sediments and palynological records indicate re‐growth of the forest after ∼900 a BP. This increased forest vegetation coincides with the timing of the decline in Maya agriculture.

Streptococcus salivarius by nasal spray for recurrent otitis: how good is the evidence? - S. Di Mario; V. Basevi; R. D’Amico; C. Gagliotti; M. Gangemi; F. Marchetti; M. L. Moro; G. Tamburlini (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

CSF lactate for accurate diagnosis of community-acquired bacterial meningitis - S. Giulieri; C. Chapuis-Taillard; K. Jaton; A. Cometta; C. Chuard; O. Hugli; R. Du Pasquier; J. Bille; P. Meylan; O. Manuel; O. Marchetti (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Mountain vegetation at risk: Current perspectives and research reeds - C. Palombo; M. Marchetti; R. Tognetti (Plant Biosystems, 2014)

Is land abandonment affecting forest dynamics at high elevation in Mediterranean mountains more than climate change? - C. Palombo; G. Chirici; M. Marchetti; R. Tognetti (Plant Biosystems, 2013)

A CAD/CAM-prototyped anatomical condylar prosthesis connected to a custom-made bone plate to support a fibula free flap - L. Ciocca; S. Mazzoni; M. Fantini; F. Persiani; P. Baldissara; C. Marchetti; R. Scotti (Medical & Biological Engineering & Computing, 2012)

Do National Parks play an active role in conserving the natural capital of Italy? - G. Capotorti; L. Zavattero; I. Anzellotti; S. Burrascano; R. Frondoni; M. Marchetti; M. Marignani; D. Smiraglia; C. Blasi (Plant Biosystems, 2012)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Multi‐taxon and forest structure sampling for identification of indicators and monitoring of old‐growth forest - C. Blasi; M. Marchetti; U. Chiavetta; M. Aleffi; P. Audisio; M. M. Azzella; G. Brunialti; G. Capotorti; E. Del Vico; E. Lattanzi; A. M. Persiani; S. Ravera; et al. (Plant Biosystems, 2010)

Influence of biochemical, mineral and morphological features of natural food on tropical cladocerans - Claudia Fileto; Marlene S. Arcifa; Juliana M. Marchetti; Izabel C. Turati; Norberto P. Lopes (Aquatic Ecology, 2007)

Influence of diatoms on copepod reproduction. III. Consequences of abnormal oocyte maturation on reproductive factors in Calanus helgolandicus - S. A. Poulet; A. Cueff; T. Wichard; J. Marchetti; C. Dancie; G. Pohnert (Marine Biology, 2007)

Progenitor cells and retinal angiogenesis - Martin Friedlander; Michael I. Dorrell; Matthew R. Ritter; Valentina Marchetti; Stacey K. Moreno; Mohammad El-Kalay; Alan C. Bird; Eyal Banin; Edith Aguilar (Angiogenesis, 2007)

Molecular markers linked to the blast resistance gene Pi-z in rice for use in marker-assisted selection - C. A. Conaway-Bormans; M. A. Marchetti; C. W. Johnson; A. M. McClung; W. D. Park (Theoretical and Applied Genetics, 2003)

A Strategy for Mapping the Heterochromatin of Chromosome 2 of Drosophila Melanogaster - Jiro C. Yasuhara; Marcella Marchetti; Laura Fanti; Sergio Pimpinelli; Barbara T. Wakimoto (Genetica, 2003)

Soybean Kunitz, C-II and PI-IV inhibitor genes confer different levels of insect resistance to tobacco and potato transgenic plants - S. Marchetti; M. Delledonne; C. Fogher; C. Chiabà; F. Chiesa; F. Savazzini; A. Giordano (Theoretical and Applied Genetics, 2000)

The effect of urea and pig slurry fertilization on denitrification, direct nitrous oxide emission, volatile fatty acids, water-soluble carbon and anthrone-reactive carbon in maize-cropped soil from the Po plain (Modena, Italy) - P. G. Arcara; C. Gamba; D. Bidini; R. Marchetti (Biology and Fertility of Soils, 1999)

Biosynthesis and cytoplasmic accumulation of a chlorinated catechol pigment during 3-chlorobenzoate aerobic co-metabolism in Pseudomonas fluorescens - F. Fava; D. Di Gioia; C. Romagnoli; L. Marchetti; D. Mares (Archives of Microbiology, 1993)